Atribusi Perilaku Pengguna Banyak Akun pada Media Sosial Instagram - Erfendy, Ulfa; Mawaddah, Mawaddah (Universitas Syiah Kuala, 2025)
The emergence of the phenomenon of using multiple Instagram accounts by one individual is increasingly widespread, especially in the younger generation. For this reason, the purpose of this research is to explain why someone has multiple accounts on Instagram and what factors cause this behavior by using Fritz Heider's attribution theory. The method used is qualitative with data collection through observation of social media content and supporting literature. The results showed that one of the reasons for having multiple Instagram accounts is due to feelings of FOMO and the desire to create an ideal self and real self. The internal factors found arise from low self-confidence and self-limitation to do self-disclosure in public spaces, making someone maintain an image by forming personal branding. While external factors come from the environment, in addition to the feeling of FOMO brought by the environment. There is also an influence on social risk, with anonymity making someone more free to express and show their real self without risking judgment. From these results, it shows that behavioral attributions of multiple account users arise from social pressure, privacy, security, functional needs and social media culture.